Analysis of Factors Adherence to Safe Injection Practice Procedures among Nurses Healthcare Center Qatar - Setiaman, Sobur; Abdullah, Syahfirin; Kholil, Kholil; Sulistyadi, Kohar (University of Muhammadiyah Semarang, 2019)
Injection practices was common medical procedure done by nurses according doctor’s prescription. In nursing process, injection practice is part of nursing intervention, but injection practices was risky for the health care workers. Needle stick injury was happened to the nurses, 18% due disposal of the needle, and 15% while draw the blood for laboratory study. Adherence to the work procedure influence by few behavior factors. Aim of research of the research were to finding out of the factors influence of adherence to safe injection practice among the nurses at healthcare center X Qatar. Type of the research was observational analytic quantities of the analytic description, using cross sectional approach. 9 variable latent with 56 variable indicator. Size of sample were 114 nurses. Data analytic with using PLS-SEM. T-statistic value on variable culture 2.94; environment 1.99; work procedure 3.81 and supervisory 3.10. T-statistic of Individual characteristic, work facility, attitude, and knowledge bellow 1.96. R2 variable adherence were showed 96.05% with Q2 87.07%. Culture, environment, work procedure and supervisory influenced of the adherence safe injection practice among the nurses. (96.05%) variable independent influence of the adherence safe injection practice among the nurses, within 87.07% showed good predicted.